Comparison of prenatal attachment levels in smoking and non-smoking pregnant women - Kartal, Zeynep; Kocataş, Semra (Journal of Dependence, 2023)
Objective: This study aimed to compare prenatal attachment levels between smoker and non-smoker pregnant women. Method: In this comparative-descriptive study, a total of 160 pregnant women (80 smokers-80 non-smokers), who were between 18-35 years of age, had their first pregnancy, were at or above 20 weeks of gestation, and had no chronic health problems or communication problems, among the pregnant women who applied to Family Health Centers for pregnancy follow-up. The data were collected using a Participant Screening Form, the Fagerstrom Test for Nicotine Dependence, Prenatal Attachment Inventory. Results: Although there was no significant difference, it was determined that the attachment scores of non-smokers were higher than those of smokers. A negative correlation was found between nicotine addiction levels and motherinfant attachment levels of pregnant smokers. Bivariate logistic regression analysis revealed that the effect of smoking during pregnancy on prenatal mother-infant attachment (Odds Ratio=0.010; p=0.999) was insignificant. Conclusion: Although the effect of smoking during pregnancy on prenatal attachment was insignificant, it was revealed that the nicotine addiction of pregnant women who smoked during pregnancy reduced prenatal attachment. Strengthening prenatal attachment may be a promising new approach to interventions for smoking cessation during pregnancy. At the same time, not smoking during pregnancy can strengthen prenatal attachment.